1988
DOI: 10.1080/01688638808402794
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among CT scans, neurological exam, and neuropsychological test performance in right-brain-damaged stroke patients

Abstract: Right-hemisphere stroke rehabilitation inpatients were assessed by: (1) CT scans; (2) neurological exam; and (3) cognitive and affective psychometric measures. Damage to temporal, parietal, and occipital regions was associated with visual-spatial impairments. Surprisingly, parietal damage was no more related than temporal and occipital damage to severity of visual inattention. While the neurologist's ratings of lability and depression were related to CT-scan measures, patients' self-report of depression was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 23 publications
5
11
0
1
Order By: Relevance
“…Although the TO area is close to the TPO junction that is known to be related to neglect, it barely included the parietal areas. These parietal areas did not correlate with neglect severity, which supports a previous study [29] where the extent of parietal damage did not correlate with neglect severity. A study using CT scan also suggested that the temporal lobe (especially middle temporal) may be as important as the parietal lobe [30].…”
Section: Discussionsupporting
confidence: 77%
“…Although the TO area is close to the TPO junction that is known to be related to neglect, it barely included the parietal areas. These parietal areas did not correlate with neglect severity, which supports a previous study [29] where the extent of parietal damage did not correlate with neglect severity. A study using CT scan also suggested that the temporal lobe (especially middle temporal) may be as important as the parietal lobe [30].…”
Section: Discussionsupporting
confidence: 77%
“…De Renzi & Spinnler (1966) suggested a right hemisphere bias for the Embedded Figures Test (EFT) as well as a greater sensitivity to anterior as opposed to posterior lesions (Egelko et al, 1988). Russo and Vignolo (1967) found that left hemisphere patients with aphasia also performed poorly on EFT whereas left hemisphere patients without aphasia performed like normal controls.…”
Section: Verbal-spatial Relationsmentioning
confidence: 98%
“…Emotional processing at the behavioral level involves strategies (nonverbal, integrative, synthetic, holistic and gestalt) and functions (pattern perception, visuospatial organization and visual imaging) for which the neuroanatomical design and the neuropsychological organization of the right hemisphere are better suited [6]. The right cerebral hemisphere has been described as having greater ability to perform intermodal integration [9], greater interlobular organization [10], stimulus-evoked physiological activity [11] and functional interconnectivity among regions compared to the left hemisphere [12]. Heilman [13] suggested that the right hemisphere is more in touch with subcortical systems that are important for emotion processing.…”
Section: Theories Of Hemispheric Specialization Of Emotionmentioning
confidence: 99%